Familial Hyperparathyroidism – Disorders of Growth and Secretion in Hormone-Secretory Tissue - Marx, Stephen J.; Lourenço, Delmar Muniz, Jr (Hormone and Metabolic Research, 2017)
Six syndromes of familial hyperparathyroidism are compared: 1) Familial hypocalciuric hypercalcemia (FHH) expresses primary hyperparathyroidism (PHPT) beginning at birth with lifelong hypercalcemia. There is nonsuppressed PTH secretion from outwardly normal parathyroid glands. It reflects germline heterozygous mutation in CASR, GNA11, or AP2S1. 2) Neonatal severe primary hyperparathyroidism is severest of the six syndromes. It requires urgent total parathyroidectomy in infancy. It usually reflects biallelic inactivation of the CASR. 3) Multiple endocrine neoplasia type 1 (MEN1) is most frequently expressed as PHPT with asymmetric enlargement of 3–4 parathyroids. Benign or malignant tumors may occur among 30 other tissues. It is predisposed by germline inactivation of MEN1 or rarely by inactivation of a cyclin dependent kinase inhibitor, and then termed MEN4. 4) Multiple endocrine neoplasia type 2A from RET activating mutation rarely presents as familial hyperparathyroidism, because medullary thyroid cancer and pheochromocytoma are more prominent. 5) Hyperparathyroidism-jaw tumor syndrome (HPT-JT) has frequent PHPT and benign jaw tumors. Twenty percent develop parathyroid cancer. It is predisposed by inactivating mutation in CDC73. 6) Familial isolated hyperparathyroidism causes multiple parathyroid tumors. It can be an incomplete expression of FHH, MEN1, HPT-JT or even of relatives without a shared driver mutation. However, in 20% of families it reflects GCM2 activating mutation. Five of the PHPT syndromes reflect overgrowth of parathyroid tissue; in contrast, familial hypocalciuric hypercalcemia reflects dysregulation of PTH secretion with little or no parathyroid overgrowth. These differences underlie major differences in clinical expression.
Keywords: endocrine neoplasia; hypercalcemia; CDC73; CASR; MEN1; GCM2